Computational Fluid Dynamics and Experimental Study of Lock-in Phenomenon in Vortex-Induced Motions of a Cell-Truss Spar - 王颖 杨建民 吕海宁 (Shanghai jiao tong da xue xue bao, 2009)
Spar platforms could be subject to vortex-induced-motions （VIM） in certain current conditions. Lockin is a phenomenon which occurs in a range of reduced velocities in VIM. In this paper, a new concept of spar platform called cell-truss spar is studied using both computational fluid dynamics （CFD） and model test to investigate the VIM of the spar under different reduced velocities. The unique configuration of the cell-truss spar is carefully considered, and the unsteady flow around the spar is calculated and visualized in CFD simulations. A physical model with a scale ratio of 1：100 of the cell-truss spar is fabricated, and model tests are carried out in the current-generating ocean engineering basin. Many important parameters in VIM of the cell-truss spar are obtained, the occurrence of lock-in phenomenon is successfully simulated, and the mechanism and rules of lock-in are analyzed.